Risk Factor for Postpartum Hemorrhage in The Post-Disaster (2019-2021) - Sitti Radhiah; Nur Khairul Fatassya; Hasanah Hasanah; Elvaria Mantao (Media Publikasi Cendekia Indonesia, 2023)
The earthquake disaster in Palu in 2018, followed by the pandemic in 2020, caused mobility to be hampered and affected people's habits and lifestyles, who mostly stayed at home and had no activities. This also affected pregnant women who just stayed at home because they were afraid. The impact of the pandemic will result in less physical activity and less interaction with health workers, causing pregnant women to experience macrosomia. This research aims to determine the risk factors for postpartum hemorrhage at Anutapura Public Hospital in Palu. This research was an analytic observational with a case-control approach. Case subjects were mothers who experienced postpartum hemorrhage, and controls were mothers who did not experience postpartum hemorrhage. Case samples were 67 people, and controls were 67 people with age matching. A simple random sampling technique was carried out for sampling. The data source used secondary data, medical records for 2019-2021. Data analysis used the odds ratio test. The results showed that macrosomia (OR=4.543 and CI=1.421-14.528), prolonged labor (OR=3.674 and CI=1.720-7.850), and parity (OR=2.452 and CI=1.199-5.014) a risk factor for postpartum hemorrhage. Postpartum hemorrhage is significantly associated with low-risk macrosomia, low-risk parity, and safe parity